2019
DOI: 10.1002/cbic.201900065
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Enzymatic Treatment and Mass Spectrometric Analysis for Identification of Glucuronidated Metabolites in Human Samples

Abstract: Glucuronidation is the most common phase II modification and plays an important role in human clearance metabolism. Glucuronidated metabolites have also been linked to disease development and microbiota–host co‐metabolism. Although many of these compounds have been identified, the total number of unknown glucuronides and their impact on the human host's physiology can only be estimated. Herein, we describe the combination of an untargeted metabolomics analysis and enzymatic metabolic conversion for the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Modifications such as acetylation, glucuronidation, sulfation, and glycine conjugation occur frequently not only on large molecules , but also on small molecular metabolites. Modifications can change structures and bioactivities of metabolites, which are very often directly linked to consequences of pathophysiological processes . It has been reported that alterations of modified metabolites are associated with the progression of many human diseases, such as prostate cancer, breast cancer, liver cancer, and end-stage renal disease .…”
Section: Introductionmentioning
confidence: 99%
“…Modifications such as acetylation, glucuronidation, sulfation, and glycine conjugation occur frequently not only on large molecules , but also on small molecular metabolites. Modifications can change structures and bioactivities of metabolites, which are very often directly linked to consequences of pathophysiological processes . It has been reported that alterations of modified metabolites are associated with the progression of many human diseases, such as prostate cancer, breast cancer, liver cancer, and end-stage renal disease .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The main research interest of phase II modications has been for the metabolism of drugs, nutritional components, toxins, and doping agents. [6][7][8][9][10] Phase II modications have recently also been linked to the cometabolism of the gut microbiome with their human host. Mainly sulfation but also glucuronidation are important modications for metabolites derived from the co-metabolism of the microbiome and its host.…”
Section: Introductionmentioning
confidence: 99%
“…22 The development of chemical biology tools in this newly developed research field is limited in comparison with other well-established 'omics' fields. [23][24][25][26][27] These tools are required to allow for selective and advanced metabolite analysis. Chemoselective modification strategies for targeted carbonyl metabolite analysis represent an effective approach to facilitate detection and identification of a metabolite class of interest.…”
Section: Introductionmentioning
confidence: 99%